2022
DOI: 10.1007/s11894-022-00835-8
|View full text |Cite
|
Sign up to set email alerts
|

Models to Predict Development or Recurence of Hepatocellular Carcinoma (HCC) in Patients with Advanced Hepatic Fibrosis

Abstract: Purpose of Review Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death in the United States (U.S.).1 The purpose of this review is to highlight published models that predict development of HCC and estimate risk of HCC recurrence after treatments. Recent Findings There have been several models created for both de novo HCC and HCC recurrence, with the more recent models using a combination of age, sex, decompensation, and laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In contrast, Du et al [44] found that elevated NLR is associated with HCC development in cirrhotic patients with HBV who underwent splenectomy for hypersplenism. Yilma et al [45] suggested that NLR was a component of HCC development and recurrence risk models in the context of CHCV. Currently, PLR showed no signi cant differences among the three groups, which disagrees with Catanzaro et al [46] who inferred PLR to be used as a predictive marker for LC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Du et al [44] found that elevated NLR is associated with HCC development in cirrhotic patients with HBV who underwent splenectomy for hypersplenism. Yilma et al [45] suggested that NLR was a component of HCC development and recurrence risk models in the context of CHCV. Currently, PLR showed no signi cant differences among the three groups, which disagrees with Catanzaro et al [46] who inferred PLR to be used as a predictive marker for LC.…”
Section: Discussionmentioning
confidence: 99%
“…Height and weight are often used to evaluate the nutritional status of individuals. Yilma et al [ 25 ] reported that a low body mass index is associated with HCC development and recurrence. Fischer et al [ 26 ] proposed that overweight and obesity are more conducive to short-term prognosis after major hepatectomy than a normal body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…In a 5-year cohort of transplant candidates monitored from first cycle LDT, multivariate analysis of TTP revealed albumin level prior to first cycle was the only HCC-independent variable associated with TTP risk. Albumin is a well-known risk factors for developing HCC [ 14 ] and, when incorporated into the ALBI grade and several other prognostic scores, can stratify PFS and OS outcomes following LDT as well as OS and RFS after hepatectomy or LT (recently reviewed in [ 15 , 16 , 17 , 18 ]). There have been far fewer studies investigating a direct relationship between albumin and HCC progression independent of overall mortality.…”
Section: Discussionmentioning
confidence: 99%